Upaya Guru Dalam Menumbuhkan Kontrol Diri Anak Melalui Kegiatan Terstruktur Di KB Aisyiyah Karangasem 01 Paciran - Mau’udatul Mamnunah; Ujang Maulana Yusup (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to determine the effectiveness of teachers' efforts in fostering children's self-control through structured activities at KB Aisyiyah Karangasem 01 Paciran. The method used is classroom action research with two cycles, where each cycle involves planning, implementation, observation, and reflection. Data were collected through observation and assessment of self-control aspects including focus and concentration, emotional regulation, adherence to rules, as well as discipline and turn-taking. The results show a significant improvement in all self-control indicators from cycle 1 to cycle 2, with the overall average score increasing from 79.9 to 96.8. The implementation of learning strategies involving short and varied sessions, a conducive learning environment, emotional regulation exercises, consistent rule repetition, and habituation of discipline and turn-taking through role-playing methods proved effective in developing children's self-control. In conclusion, structured activities designed and consistently implemented by teachers can comprehensively enhance children's self-control and support the socio-emotional development of early childhood.